Centaurea stuessyi (Compositae: Cardueae), a new species from the eastern Iberian Peninsula - Arnelas, Itziar; Devesa, Juan Antonio; López, Eusebio (Phytotaxa, 2013)
Centaurea stuessyi is described as new to science from the eastern Iberian Peninsula, Spain. The range of this new species coincides with the zone of overlap of the ranges of two related species, C. antennata (subsp. antennata) and C. linifolia. The chromosome number found in the new species (2n = 44) reinforces its differences from C. linifolia (2n = 22) and C. antennata (2n = 22). The new species is compared with related species, and a description is given of its ecological preferences.